RUINS AS TROPES OF MODERNITY - GHEORGHIU, Dragoş (Design/Arts/Culture, 2020)
Ruins were a fascinating subject for the last half-millennium culture in Europe. Their rhetoric structure, determined by the work of Nature-Time upon materials, stimulated the arts and architecture between the Middle Ages and Post-Modernism. The paper discussed the analogy between the human body and architecture, together with the material tropes identified in iconography and illustrated with two iconic sites, Petra and Jerash. An example presented to show the use of the tropes of ruins in creating Modern Art is Constantin Brancusi’s monumental work for the World War’s I soldiers.